Some considerations on the scientific research method in sport - Sampedro Molinuevo, Javier (SPORT TK-EuroAmerican Journal of Sport Sciences, 2013)
The purpose of the present article is to give an overview of scientific research in performance sport and at the same time adopt a position in a science which analyzes Play Action with regard to the transversality of other sciences starting with interdisciplinary sports knowledge and middle range theory. The different methodological designs are explained theoretically with concrete applications in different sports whether individual, opposition, association and association/opposition.